Peran guru dalam menghadapi tantangan teknologi era digital - Hafid, Nasya (Maliki Interdisciplinary Journal, 2024)
The role of teachers is very important and complex in facing the technological challenges of the digital age. Teachers must have the ability and skills to apply the right solutions to face various problems in the digital world. They must have the ability to evaluate, improve, process and be able to use digital information. Teachers must also be able to analyze various problems faced by students and be able to provide methods that help learning activities. In addition, teachers must also have awareness of technology that is growing rapidly and be able to improve the quality of learning by using various digital learning devices and resources. During this period, teachers are not only facilitators, but also motivators, guides, information providers and evaluators in providing guidance and opportunities to students. Therefore, the role of teachers is very important in facing the challenges of digital technology and requires high abilities and skills